Implementation of Project Based Learning Model with Windows Movie Maker Media in Improvement of Short Story Writing - R. Panca Pertiwi Hidayati; Siti Nurjanah (STKIP Singkawang, 2017)
This research is motivated by the lack of ability of students in writing short stories. This research apply project based learning model with windows movie maker media. The formulation of the problem is